A Gradient-Gated SPAD Array for Non-Line-of-Sight Imaging - Zhao, Jiuxuan; Gramuglia, Francesco; Keshavarzian, Pouyan; Toh, Eng-Huat; Tng, Michelle; Lim, Louis; Dhulla, Vinit; Quek, Elgin; Lee, Myung-Jae; Charbon, Edoardo (Institute of Electrical and Electronics Engineers, 2024)
Time-resolved non-line-of-sight (NLOS) imaging based on single-photon avalanche diode (SPAD) detectors have demonstrated impressive results in recent years. To acquire adequate number of indirect photons from a hidden scene in the presence of overwhelming amount of early-arrival photons, a single-gated SPAD is widely employed to mitigate pile-up. However, additional prior knowledge of the hidden range and relay surface profile are required to preset the gating position and implement the reconstruction. With this work, we propose a gradient-gated technique to alleviate these shortcomings (pile-up and prior knowledge) in NLOS imaging with the development of a 6 × 6 SPAD array fabricated in a standard 55-nm Bipolar-CMOS-DMOS (BCD) technology. The SPAD sensor includes a delay-locked loop (DLL) block, a gating generator and a pixel array, which can be flexibly configured to free-running, single-gating and gradient-gating modes. The rise time of the gates is less than 450 ps (from 10% to 90%). In gradient-gating mode, the interval time between adjacent gates can be configured from 300 ps to 2 ns. In single-gating mode, the minimum gate window is measured below 5 ns. We demonstrated the sensor in a confocal NLOS imaging system that reconstructs hidden scenes with both retroreflective and diffuse objects. The presented scheme enables the development of calibration-free NLOS imaging modality for practical applications.